Portable spectral Doppler echocardiographic device: overcoming limitations. Issue 9 (15th August 2003) - Quiles, J; García-Fernández, M Á; Almeida, P B; Pérez-David, E; Bermejo, J; Moreno, M; Avanzas, P
Abstract : Background: There is evidence that new portable echocardiographic devices are useful in evaluating heart anatomy and function, but a lack of Doppler modes has up to now been an important limitation in obtaining haemodynamic data. Objectives: To report the Doppler capabilities of a new hand held echocardiographic device. Design: Blinded comparison of two types of echocardiography machine. Setting: Tertiary care centre. Patients: 98 consecutive patients were randomly imaged with the hand held device, with a standard platform as reference. Outcome measures: Pulsed wave transmitral Doppler inflow tract velocities, deceleration time, and continuous wave Doppler measurements of aortic ejection and tricuspid regurgitation peak velocities were recorded. Results: There was excellent agreement between the hand held device and standard echocardiography for the evaluation of diastolic E and A waves, E/A ratio, and deceleration time with pulsed wave Doppler (intraclass correlation coefficients of 0.97, 0.93, 0.90, and 0.78, respectively). In addition, good agreement was found between continuous wave Doppler measurements of aortic ejection and tricuspid regurgitation velocities (intraclass correlation coefficients of 0.96 and 0.80). However, there was a significant difference between patients with tricuspid regurgitation measured with the hand held device (25.5%) and by standard echocardiography (65.3%), resulting in misdiagnosis of eight patients with pronounced pulmonary hypertension. Conclusions: New hand held devices with Doppler capabilities overcome previous limitations in evaluating haemodynamic variables. With colour Doppler they are now suitable for the complete evaluation of valvar disease and diastolic function. However, important limitations remain in the evaluation of pulmonary pressures.